FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nadya Suryana; Frestin Chrisnanti (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to find empirical evidence related to the influence of firm size, return on assets (ROA), managerial ownership, sales growth, dividend policy, and debt policy on firm value as proxied by Tobin's Q. The sample in this study was selected using the purposive sampling method and totaled 59 non financial companies listed on the Indonesia Stock Exchange (IDX) in the period 2018 to 2020. The hypothesis testing in this study used the multiple regression method. The results of this study indicate that only return on assets have an effect on firm value. Meanwhile, the variables of firm size, managerial ownership, sales growth, dividend policy, and debt policy have no effect on firm value.